The logopenic variant of primary progressive aphasia - Henry, M.L. (2010)
PURPOSE: The aim of this review is to explore the evolution of the logopenic variant of primary progressive aphasia as a distinct clinical entity and to outline recent advances that have clarified its clinical characteristics, neural underpinnings and potential genetic and pathological bases. This is particularly relevant as researchers attempt to identify clinico-pathological relationships in subtypes of primary progressive aphasia in hopes of utilizing language phenotype as a marker of underlying disease. RECENT FINDINGS: Recent work has served to refine and expand upon the clinical phenotype of the logopenic variant. Logopenic patients show a unique pattern of spared and impaired language processes that reliably distinguish this syndrome from other variants of progressive aphasia. Specifically, they exhibit deficits in naming and repetition in the context of spared semantic, syntactic and motor speech abilities. Further, there is a growing body of evidence indicating a possible link between the logopenic variant phenotype and specific pathological and genetic correlates. SUMMARY: Findings indicate that the logopenic variant is a distinct subtype of progressive aphasia that may hold value as a predictor of underlying pathology. Additional research, however, is warranted in order to further clarify the cognitive-linguistic profile and to confirm its relation to certain pathological and genetic processes.